'A learning experience': Disciplinary and parenting practices among Native American families. Issue 2 (2nd August 2021) - McKinley, Catherine; Knipp, Hannah; Lilly, Jenn
Abstract: Research indicates that effective disciplinary practices, such as offering praise and teaching acceptable versus non‐acceptable behaviour, can act as protective factors against the social and behavioural health disparities experienced by Native Americans (NA). The purpose of this critical ethnographic study ( n  = 436 qualitative elder, adult, youth and professional participants) was to use the Framework of Historical Oppression, Resilience, and Transcendence (FHORT) to qualitatively examine participants' reported experiences of disciplinary practices. Thematic analysis of qualitative results indicated several approaches to disciplining children, which included the following themes: (a) Establishing Structure and Boundaries; (b) Taking Away Privileges and Rewarding Good Behavior; and (c) Teaching Right from Wrong. Results indicate that despite experiencing historical oppression, NAs still report many disciplinary and other parenting practices contributing to family resilience that were present prior to colonization. Communal and relational supports contribute to positive parenting practices, indicating an importance to promote holistic and inclusive clinical treatment approaches.